Impact of Antenatal Care on Maternal and Perinatal utcome: A Study at Nepal Medical College Teaching Hospital - Tuladhar, H; Dhakal, N (Nepal Journal of Obstetrics and Gynaecology, 2012)
Aims: To identify the determinants of antenatal care (ANC) attendance and its impact on maternal / perinatal outcome. Methods: Prospective descriptive study of women delivered at Nepal Medical College Teaching Hospital (NMCTH), a 700 bedded tertiary care hospital situated at periphery of Kathmandu. Results: Among 322 women delivered during period of four months, majority (87%) reported of attending more than 4 antenatal visits, only 21 (6.5%) women had not attended ANC. The most preferred place of ANC was hospital (71.6%). Women with secondary education and above, business/service holders, 20-29 years age group, primigravida and Brahmin / Chhetri caste were more likely to attend ? 4 visits, while those living further than 6 km. from a health facility were less likely to attend. Financial problem (52.4%) followed by ignorance (28.6%) were the most commonly stated reasons for not attending ANC. Women attending more than 4 antenatal visits have more chance of full immunization with tetanus toxoid and iron supplementation. Most of the women started attending ANC from their second trimester (75.8%), only 21.9% had first ANC visit during first trimester. Overall Cesarean section rate was 17.4% and with increased rates in women who had attended ANC, because of the fact that all elective cesarean section were planned in these women only. Also, all inductions of labor (9.3%) were performed among them. Maternal complications like anemia and pregnancy induced hypertension occurred more commonly in women without ANC. The proportion of low birth weight and preterm babies was higher in women with inadequate or no ANC. Special care baby unit (SCBU) admission was also higher among them due to various reasons like neonatal sepsis, birth asphyxia, jaundice etc. While there were no neonatal deaths during the study period, 3 still births have occurred. Perinatal mortality rate was similar in no ANC and inadequate ANC groups; it was 16 times higher than that in the group with more than 4 visits. Maternal and perinatal outcomes were found to be better in women who attended regular ANC. Conclusions: Although attendance of ANC is quite encouraging, the proportion of women attending ANC from first trimester is low. The quality of antenatal care needs to be strengthened. The health system needs to ensure the availability of ANC in primary care level and to establish mobile clinics for those living far from the health facilities. NJOG 2011 Nov-Dec; 6 (2): 37-43 DOI: http://dx.doi.org/10.3126/njog.v6i2.6755